Pengujian Tingkat Reliabilitas Metode Weight Aggregated Sum Product Assessment Menggunakan Pearson Correlation - Hidayanti Murtina; Nunung Hidayatun; Susafaati Susafaati (JURNAL TEKNIK KOMPUTER AMIK BSI, 2021)
Teacher assessment activities are common activities carried out. Evaluation of exemplary teachers is one of the activities held every year in schools, especially at PGRI Babelan Junior High School. The selection of exemplary teachers carried out by SMP PGRI Babelan must be as minimum as possible free from things that can damage the results such as conducting a subjective assessment, therefore the author conducted research using one of the multi attribute decision making methods, namely the Weight Aggregated Sum Product Assessment (WASPAS) method. . The criteria used in the selection of exemplary teachers at SMP PGRI Babelan include Ethics, Methods and Didactics, Responsibility, Credibility, Absence with the stages of the Weight Aggregated Sum Product Assessment (WASPAS) method itself consisting of matrix normalization stages, searching for the value of Qi (1) namely the value of the Weighted Sum Model (WSM), the search for the value of Qi (2), namely the value of the Weighted Product Model (WPM) and the stages of the Weight Aggregated Sum Product Assessment (WASPAS) method itself so that it is found that the 6th alternative is the teacher most recommended by the method. Weight Aggregated Sum Product Assessment (WASPAS) with a value of 0.9860 followed by the 1st alternative with a value of 0.8907 and re-tested the level of reliability using Pearson Correlation